Nanotechnology-Based Targeting of mTOR Signaling in Cancer - Yoon MS (International Journal of Nanomedicine, 2020)
Mee-Sup Yoon Department of Molecular Medicine, School of Medicine, Lee Gil Ya Cancer and Diabetes Institute, Department of Health Sciences and Technology, GAIHST, Gachon University, Incheon 21999, Republic of KoreaCorrespondence: Mee-Sup Yoon Tel +82-32-899-6067Fax +82-32-899-6039Email msyoon@gachon.ac.krAbstract: Mammalian target of rapamycin (mTOR) is a master regulator of cell growth and metabolism, which is activated in response to intra- and extracellular signals, including nutrients, growth factors, and cellular energy levels. The frequent dysregulation of mTOR signaling in cancer makes it an attractive therapeutic target, and several types of mTOR inhibitors have been developed. Nanoparticle-based mTOR modulators are predicted to target various cancers and deliver as well as release drugs in a controlled manner, resulting in enhanced bioavailability and reduced side effects. This mini-review is focused on the molecular mechanism of nanoparticle-based mTOR modulator action as well as the current development of mTOR inhibitors using nanoparticles. Understanding the biological function of nanoparticle-based mTOR modulators will contribute to the development of efficient nano-therapeutics for the treatment of cancers.Keywords: mammalian target of rapamycin, cancer, rapalogs, mTOR kinase inhibitor, RapaLinks, nanotechnology, nanoparticles